Financial Performance Evaluation: The Role of ROA and ROE in Increase Company Value - Nurjanah, Siti; Wijaya, Steven Natanael; Komara, Acep; Mahadianto, Moh Yudi (International Journal of Business, Economics, and Social Development, 2025)
This research aims to evaluate the financial performance of companies that go public in the banking sector by prioritizing the role of profitability variables in determining the value of the company. The indicators used are ROA and ROE which are important indicators used to measure the level of profitability and efficiency of a company in managing its assets and equity. In this study, quantitative data was obtained from the financial statements of several banks listed on the Indonesia Stock Exchange (IDX) in a certain period. To test the relationship between Return on Assets (ROA), Return on Equity (ROE), and company value, multiple regression analysis was used. The results show that ROA has a significant effect on company value, while ROE does not show a significant influence. These findings emphasize the importance of the role of banking management in optimizing ROA to increase the company's value in the eyes of investors.